The amber-colored liquid: A review on the color standards, methods of detection, issues and recommendations - Hasnul Hadi M.H.; Ker P.J.; Thiviyanathan V.A.; Tang S.G.H.; Leong Y.S.; Lee H.J.; Hannan M.A.; Jamaludin M.Z.; Mahdi M.A. (MDPI, 2023)
Amber; Colorimetry; Liquids; Signal processing; Color measurements; Color standards; Condition; Customer preferences; Detection; Liquid products; Measurement techniques; Measurements of; Objective methods; Subjective methods; Color; color; forecasting; standard; Color; Forecasting; Reference Standards